Determinants and policy approaches to healthcare professional retention in Iran: A mix of scoping review and qualitative evidence - Hamideh Keyvani; Reza Majdzadeh; Jalal Hanaee; Leila Doshmangir (PLoS ONE, 2026)
Background Ensuring the long-term retention of healthcare professionals has become a central priority for strengthening the resilience and quality of Iran’s health system. A comprehensive understanding of the diverse factors influencing retention, alongside those that may contribute to outward mobility, is essential for informed policymaking. This study adopts a multi-method approach, integrating qualitative inquiry with a scoping review, to explore the determinants shaping healthcare professionals’ decisions to remain in or leave the national health system, the implications for workforce stability, and the effectiveness of current policy responses. By examining both individual and systemic dimensions, and by incorporating insights from migrant professionals, domestic policymakers, and existing evidence, this research contributes a nuanced perspective to the broader discourse on human resources for health in developing contexts. The originality of this study lies in combining first-hand qualitative data with a systematic synthesis of literature, allowing for an in-depth understanding of locally grounded drivers of retention and opportunities for strengthening Iran’s health workforce. Methods The research employed a qualitative, multi-phase design. In the first phase, semi-structured interviews were conducted with 15 Iranian healthcare professionals residing in countries such as the United States, Germany, Switzerland, Turkey, and Oman to understand their professional trajectories. In the second phase, interviews with 16 Iranian health administrators, policymakers, and senior professionals were undertaken to capture institutional and policy-level perspectives on retention challenges and opportunities. All interviews were transcribed verbatim and analyzed thematically. Complementing this, a scoping review was conducted to synthesize existing evidence, policy documents, and expert assessments related to the retention and mobility of Iran’s health workforce. Data sources included PubMed, Scopus, and gray literature obtained through institutional repositories and local websites. Results Findings highlight several interrelated factors influencing workforce retention. Economic considerations including income stability, purchasing power, and access to research funding remain important determinants of professional commitment. Institutional dynamics such as transparent promotion pathways, supportive management, and opportunities for professional development also play a critical role. Importantly, Iran’s integrated system of medical education and service delivery emerged as a key structural strength, providing early clinical exposure, strong professional identity formation, and continuity between training and practice advantages less commonly available in many other health systems. Participants noted that when financial incentives are combined with accessible professional development programs, equitable workload distribution, and recognition of professional contributions, retention outcomes improve substantially. While destination countries may offer expanded career pathways, the sense of belonging, family ties, and cultural identity were identified as influential factors supporting continued service in Iran. Governmental initiatives including compensation adjustments, training reforms, and targeted retention programs have yielded positive outcomes, though further coordination and sustained implementation are needed. Conclusion Strengthening the retention of healthcare professionals in Iran requires a holistic strategy that integrates economic, organizational, educational, and governance reforms. Enhancing remuneration structures, investing in professional development and research capacity, reinforcing the advantages of Iran’s integrated educational service system, and engaging with the healthcare diaspora can collectively support workforce stability. A multi-sectoral, evidence-informed approach has the potential to improve long-term retention, mitigate the need for outward mobility, and promote a more resilient and sustainable health system.